The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1365-2826.2008.01737.x
|View full text |Cite
|
Sign up to set email alerts
|

The Placenta is Simply a Neuroendocrine Parasite

Abstract: This paper will document the early scientific observations that kindled my neuroendocrinological interest in pre‐eclampsia, a life‐threatening disease that affects both mother and baby. My interest in this subject started with the placental origin of melanotrophin activity, moving on, through corticotrophin‐releasing factor and its binding protein, to a tachykinin modified specifically in the placenta by phosphocholine, a post‐translational moiety normally used by parasites to avoid immune surveillance and rej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Instead the predominant NKB-like immunoreactivity was found in peaks of much larger molecular mass. A similar observation has also been reported by Lowry [43] who observed that the placental concentrations of processed NKB peptides from normal pregnancies were very low and extracts contained more partially processed material than fully processed products. This was also evident in the maternal blood where NKB precursor peptides could also be found [43].…”
Section: What Is the Cause Of The Elevated Levels Of Nkb During Pre-esupporting
confidence: 87%
See 1 more Smart Citation
“…Instead the predominant NKB-like immunoreactivity was found in peaks of much larger molecular mass. A similar observation has also been reported by Lowry [43] who observed that the placental concentrations of processed NKB peptides from normal pregnancies were very low and extracts contained more partially processed material than fully processed products. This was also evident in the maternal blood where NKB precursor peptides could also be found [43].…”
Section: What Is the Cause Of The Elevated Levels Of Nkb During Pre-esupporting
confidence: 87%
“…A similar observation has also been reported by Lowry [43] who observed that the placental concentrations of processed NKB peptides from normal pregnancies were very low and extracts contained more partially processed material than fully processed products. This was also evident in the maternal blood where NKB precursor peptides could also be found [43]. In contrast the chromatographic profiles from term pre-eclamptic placenta had a single peak that contained significant amounts of processed NKB that corresponded to that of NKB found in the rat brain and to that of synthetic NKB [24,27].…”
Section: What Is the Cause Of The Elevated Levels Of Nkb During Pre-esupporting
confidence: 87%
“…The various mechanisms of maternal immune tolerance include: complement inhibition, 59 phosphocholination, 60 upregulation of programmed death ligand-1 over CD4/ CD8 CTLs, 61 alteration of processing and presentation by Major histocompatibility complex, progesterone, 62 shift in Th-1/Th2 cytokine balance, Tregs (regulatory T cells) and placental exosomes. The role of these mechanisms of maternal immune tolerance is still unfolding.…”
Section: Normal Pregnancy: Mechanisms Of Immune Tolerancementioning
confidence: 99%
“…In these studies, placental neurokinin B and the precursors of corticotropin releasing hormone (CRH), adrenocorticotropin, hemokinin, activin and follistatin were shown to be post-translationally modified by the addition of phosphocholine using a combination of HPLC and two site immunometric analyses. Lowry (Lowry, 2008) suggested that the addition of phosphocholine moieties in placental secreted peptides and proteins may be the rule rather than the exception and that this post translational modification may play an important role in maternal immune tolerance during pregnancy.…”
Section: Phosphocholinationmentioning
confidence: 99%